Japanese governance : beyond Japan Inc. - Amyx, Jennifer Ann; Drysdale, Peter (Politics in Asia series., 2003)
This interdisciplinary book gathers contributions from experts in political science, economics, law and Japanese studies to give a deeper understanding of how Japan's political economy and policymaking processes are working today.